Exploring the N2 Adsorption and Activation Mechanisms over the 2H/1T Mixed-Phase Ultrathin Mo1-xWxS2 Nanosheets for Boosting N2 Photosynthesis - Qin, Jiangzhou; Zhao, Wenjun; Hu, Xia; Li, Jiang; Ndokoye, Pancras; Liu, Baojun (ACS applied materials & interfaces, 2021)
Solar-driven conversion of nitrogen (N2) to ammonia (NH3) is highly appealing, yet in its infancy, the low photocatalytic efficiency and unclear adsorption and activation mechanisms of N2 are still issues to be addressed. In this study, ultrathin alloyed Mo1-xWxS2 nanosheets with tunable hexagonal (2H)/trigonal (1T) phase ratios were proposed to boost photoreduction N2 efficiency, while the mechanisms of N2 adsorption and activation were explored simultaneously. The alloyed Mo1-xWxS2 nanosheets for the 1T phase concentration of 33.6% and Mo/W = 0.68:0.32 were proven to reach about 111 μmol gcat-1 h-1 under visible light, which is 3.7 (or 3)-fold higher than that of pristine MoS2 (or WS2). With the aid of density functional theory calculations and in situ N2 adsorption X-ray absorption near-edge fine structure techniques, the adsorption and activation behaviors of N2 over the interface of Mo1-xWxS2 nanosheets were investigated during the N2 reduction process. The results show that the W doping causes a higher electron density state in W 5d orbitals, which can further polarize the adsorbed N2 molecules for adsorption and activation. This work provides a new insight into the adsorption and activation mechanisms for the NH3 synthesis.Solar-driven conversion of nitrogen (N2) to ammonia (NH3) is highly appealing, yet in its infancy, the low photocatalytic efficiency and unclear adsorption and activation mechanisms of N2 are still issues to be addressed. In this study, ultrathin alloyed Mo1-xWxS2 nanosheets with tunable hexagonal (2H)/trigonal (1T) phase ratios were proposed to boost photoreduction N2 efficiency, while the mechanisms of N2 adsorption and activation were explored simultaneously. The alloyed Mo1-xWxS2 nanosheets for the 1T phase concentration of 33.6% and Mo/W = 0.68:0.32 were proven to reach about 111 μmol gcat-1 h-1 under visible light, which is 3.7 (or 3)-fold higher than that of pristine MoS2 (or WS2). With the aid of density functional theory calculations and in situ N2 adsorption X-ray absorption near-edge fine structure techniques, the adsorption and activation behaviors of N2 over the interface of Mo1-xWxS2 nanosheets were investigated during the N2 reduction process. The results show that the W doping causes a higher electron density state in W 5d orbitals, which can further polarize the adsorbed N2 molecules for adsorption and activation. This work provides a new insight into the adsorption and activation mechanisms for the NH3 synthesis.